Nízkokarbonové technologie v distribučních sítích - Essa, Abdullah; Abdullah Essa (České vysoké učení technické v Praze, 2020)
Abnovitelné zdroje energie (OZE) v distribučních soustavách (DS) nabývají na důležtitosti a v budoucnu budou hrát v DS důležitou roli. Tato diplomová práce popisuje základní informace o OZE a jejich principech činnosti. V práci je shrnuto současné i budoucí využití OZE v různých částech světa. V práci jsou také uvedena legislativní pravidla pro připojování OZE k DS. Na případové studii je ověřena připojitelnost 2 MW větrné elektrárny k DS z pohledu vyvolané napěťové změny a flikru.

Renewable energy sources (RES) are gaining an increasing importance in the distribution system and they are predicted to play a more important role in the near future. This thesis will provide general information about renewable energy sources and their working principles. The present and future usage of RES is summarized for different regions in the world. Legislation and rules about connecting into the distribution grid has been presented. Besides, a case study demonstrates the evaluation of connectivity of a 2 MW wind power plant to a distribution network from the perspective of voltage change and flicker effect.
Low-carbon technology in distribution networks
Keywords: Obnovitelné zdroje energie; výrobna elektřiny; vodní elektrárna; fotovoltaická elektrárna; větrná elektrárna; distribuční soustava; DNCalc software; ustálený chod; flikr; Renewable energy sources; Power generation; Hydropower energy; Solar energy; Wind energy; Power plants; Distribution System; DNCalc software; Load Flow; Study of connectivity; Flicker